A Retrospective Exploration of the Impact of the 'Angelina Jolie Effect' on the Single State‐Wide Familial Cancer Program in Perth, Western Australia. Issue 1 (6th June 2016) - Freedman, Rebecca; Mountain, Helen; Karina, Dian; Schofield, Lyn
Abstract: Global media has the power to influence the ways the public engage with health services. On May 14th 2013, Angelina Jolie published an article in the New York Times magazine, outlining her decision to undergo BRCA mutation testing due to a family history of cancer; then proceed with a mastectomy. The article evoked significant interest from the media and the public. During the months that followed, the Familial Cancer Program (FCP) at Genetic Services of Western Australia (GSWA) experienced a significant increase in referrals and enquiries. Resources were overstretched and it became clear we needed to adjust work practices to manage the escalating numbers. New strategies were devised to cope with the influx of enquiries, albeit without the benefit of additional resources. We conducted an audit of referrals to the FCP made between January 2012 and December 2014. This included a comparison of the months prior to and following the New York Times article. The aim of the audit was to quantify the impact of the "Angelina Jolie effect" on referrals to the FCP. Whilst the increased awareness of the role of genetic services in risk assessment and testing for familial breast and ovarian cancer was considered positive, pre‐referral risk assessment at the primary health level to evaluate the appropriateness of their patients for referral could have been helpful. Potentially, many inappropriate referrals to FCP may have been avoided with primary health evaluation thus lessening the burden on our service and preventing unnecessary worry in well women who possessed minimal family history or risk factors. It is important to understand the factors driving the uptake of risk reduction activities, particularly if engagement with a genetics service is considered part of that pathway. Continued education about cancer risk due to family history, individual features and awareness surrounding genetic testing criteria, costs and availability is required for both the public and health professionals.